2008
DOI: 10.1093/gerona/63.10.1076
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impact of 10 Days of Bed Rest in Healthy Older Adults

Abstract: In healthy older adults, 10 days of bed rest results in a substantial loss of lower extremity strength, power, and aerobic capacity, and a reduction in physical activity, but has no effect on physical performance. Identification of interventions to maintain muscle function during hospitalization or periods of bed rest in older adults should be a high priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
284
3
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(301 citation statements)
references
References 36 publications
6
284
3
8
Order By: Relevance
“…However, bed rest has deleterious effects on lean muscle mass, physical function, lower extremity strength/power, aerobic capacity and insulin sensitivity [19][20][21]. Individuals with diminished insulin sensitivity are subject to a disproportionate aggravation of existing systemic low-grade inflammation during periods of physical inactivity [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, bed rest has deleterious effects on lean muscle mass, physical function, lower extremity strength/power, aerobic capacity and insulin sensitivity [19][20][21]. Individuals with diminished insulin sensitivity are subject to a disproportionate aggravation of existing systemic low-grade inflammation during periods of physical inactivity [22].…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalization is an indicator of the occurrence of diseases that requires specialized care, which in itself results in a greater likelihood of functional incapacity. Another study (29) observed that hospitalization exposures elderly patients to a substantial decline in functional status due to the loss of lower-limb strength and decline of aerobic capacity, induced by physical inactivity and bed rest.…”
Section: Discussionmentioning
confidence: 99%
“…ACUTE HOSPITALIZATION because of illness or injury can have devastating consequences on the functional capacity and performance of activities of daily living in older adults (3,25). Profound inactivity characterizes acute hospitalization in older adults and can significantly and independently contribute to muscle and functional loss (11,12).…”
mentioning
confidence: 99%